Systematic school based assessment (SSBA) for cognitivelearning in senior secondary school economics (2009)
This study was designed to find out if the use of Systematic School Based Assessment (SSBA) could engender cognitive learning outcome in senior secondary economics in Nigerian schools using Okene local govenrment are of Kogi state, Nigeria as a sample. Three hypotheses were formulated to address the population of the investigation. Six senior secondary schools out of the twenty senior secondary schools in the area were randomly selected intact SS classes (1-3) were randomly chosen for the study. Three synthesized teacher-made tests validated by the researcher were reliability (test-retest) and validity (internal consistency) coefficients of 0.8, 0.73 and 0.68; 0.66,0.82 and 0.79 correspondingly for SS1 to SS3 respectively for both pre-test and post-test in the respective classes. Findings in the study include the fact that SSBA engendered significant improvement in the cognitive learning of students in SS economics; assists students to master the art of examination and thus likely to help in reducing the incidence of examination mal practice; keep the students busy with their study and also helped both teacher and students to discover their areas of strengths and weaknesses and to take steps either meant to strengthen their areas of strengths and ameliorate their weaknesses for better teaching effectiveness and performacnes in cognitive learning. It was thus recommended that SSBA should be adopted and encoraged in secondary schools to engender improved learning, all stakeholders in the education industry should support the use of SSBA in our secondary schools, teachers should be trained in evaluation techniques among others.